Implementation of Restorative Justice in Settlement of Hate Speech Cases through Social Media in the ITE Law - Mujianto Mujianto; Hotma P. Sibuea; Syahrir Kuba (Research Horizon, 2023)
The purpose of this research is to provide a comprehensive description of the research object, to clearly outline the state and condition of the object in order to gain a profound understanding of the situation/events and to discover patterns of relationships among situations/events, thus revealing the interconnection of data variables resulting from this study. The objective of this research is to gain an overview and understanding of how restorative justice is implemented in resolving cases of hate speech occurring in digital spaces or social media, where such criminal offenses are regulated by Law Number 11 of 2008 concerning Information and Electronic Transactions. The results highlight the implementation of restorative justice in resolving hate speech on social media, based on Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 on Information and Electronic Transactions, and analyze the challenges faced by the Police Institution in handling hate speech criminal cases on social media. The theoretical findings of this research are expected to serve as a source of information, enhance knowledge, and contribute to the field of criminal law, especially regarding the implementation of restorative justice in resolving hate speech cases conducted on social media.